Evaluation of polymerization shrinkage of dental composites by microcomputed tomography - Kamalak, Hakan; Kamalak, Aliye (Scientific Publishers of India, 2018)
Objective: The aim of this study was to evaluate the polymerization shrinkage of different commercially available dental composites with micro-computed tomography (?-CT). Method: The study group included eight different flowable composites; Surefil SDR Flow (SDR), Charisma Flow (CHF), Clearfil Majesty Flow (CMF), Vertise Flow (VF), Grandio Flow (GF), Filtek Supreme Ultimate Flow (3MEFU), Filtek Bulk Flow (3MBF), X-Tra Base Flow (XTB). Composite materials were placed in standard cylindrical teflon molds and these were scanned for 1 h using ?-CT Skyscan 1172. Polymerization was not observed during scanning since the internal chamber of the equipment was completely dark. When the scanning was complete, materials were polymerized with LED light as per producer recommendations and rescanned with Skyscan 1172 using the same parameters. After the scanning process was over, test materials were analyzed using ?-CT-CTAn software programme. Results: Data were analyzed using Kruskal Wallis, Mann Whitney U and Wilcoxon test at a significance level of ?=0.05. Polymerization shrinkage ranged between 1.44% (CMF) and 2.73% (CHF). Bulk-fill and Self-adhesive composites were significantly lower (p<0.05) than those of the others. Conclusion: All tested materials were able to achieve acceptable shrinkage at 2-4 mm depth. The higher shrinkage of hybrid composites over that of other groups may indicate a potential for higher interfacial stresses. However, the bulk fill composite showed low shrinkage that may prove less damaging to the interface. © 2018, Scientific Publishers of India. All rights reserved.
Keywords: Bulk fill; Composite resins; Micro tomography; Shrinkage